Correlation of nucleated red blood cell count with neonatal intensive care unit admission - ., Sambedna; Kumar, Amit; Chakore, Rita (International Journal of Contemporary Pediatrics, 2020)
Background: Perinatal asphyxia should be diagnosed, when baby goes on to develop hypoxic ischemic encephalopathy which has shown to be much more reliable indicator of long term handicap than any other perinatal markers like non reassuring FHR, Apgar score, meconium stained amniotic fluid and blood acid base status of fetus. Since NRBC is related to hematopoietic response to hypoxia it predicts the chance of neurological sequelae and NICU admission. The aim of our study to analyze the significant relationship of NRBC count and NICU admission. Methods: This was a retrospective comparative study conducted in department of OBG, Patna medical college and Hospital between December 2013 to November 2015 in tertiary care health centre. Umbilical cord blood samples were collected from 100 newborns with asphyxia at birth out of which 56 were admitted in NICU taken as study group and rest 44 asphyxiated babies were not admitted in NICU were taken as control group. NRBC per 100 WBC was counted in Cord blood sample from all babies. Results: This shows that average count of NRBC/100 WBC in the study with NICU admission was 27.37+7.25. Average count in the study group with no NICU admission was 23.93+6.04. The difference was statistically significant (p<0.05). Conclusions: This study concludes that NRBC count correlate well with fetal asphyxia and finally NICU admission. Early detection leads to decrease neurological morbidity and mortality among survivors.